Transformasi Konsep Kewarganegaraan di Era Digital: Implikasi Sosial, Etis, dan Masa Depan - TEGAR ZAKI HANAFI; BUDI ARDIANTO (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
This study explores the evolution of citizenship concepts in the digital era, influenced by globalization, information technology, and socio-political changes. Using an interdisciplinary approach, it identifies new patterns of citizenship, including transnational and digital citizenship, and the challenges in their application. Findings reveal that citizenship now encompasses complex identity networks that transcend national boundaries. The social and ethical implications of digital technology, such as the digital divide and privacy concerns, are analyzed to provide insights for inclusive and adaptive policies. This research enriches the citizenship literature and paves the way for further studies to build inclusive and sustainable societies in the digital age.